Real Effects of High Inflation - Braumann, Benedikt (IMF Working Papers; Working Paper, 2000)
This paper revisits the question of the real effects of inflation, on the basis of the experience with 23 high inflation episodes in 17 countries. It finds strong indications that inflation had contractionary effects on a number of important macroeconomic variables, such as GDP, investment and employment. Moreover, high inflation led to a significant decline in real wages, a real depreciation and an improvement in external trade. These patterns are consistent with explanations that stress the transaction role of money, such as models with a cash-in-advance constraint. However, some observations are hard to reconcile with existing theory, especially the large magnitude of the fall in real wages.1.